Pyogranulomatous pleuropneumonia caused by Nocardia asiatica in a dog coinfected with canine morbillivirus (canine distemper virus). Issue 1 (1st October 2019) - Teixeira Ribeiro, Allyne Isabela; da Cruz Burema, Mayara; de Souza Borges, Ana Paula; de Melo Bruno, Vanessa Cristina; Brandini Néspoli, Pedro Eduardo; Colodel, Edson Moleta; Furlan Gouvêa, Fernando Henrique; Dutra, Valéria; Nakazato, Luciano; Ribeiro, Márcio Garcia; de Aguiar, Daniel Moura
Abstract: Nocardia asiatica causing pyogranulomatous pleuropneumonia is reported for the first time in a dog coinfected with canine morbillivirus (CM), diagnosed based on epidemiological, clinical, haematological, images, microbiological, histopathological, polymerase chain reaction and hsp 65 gene sequencing findings. The immunosuppression of CM probably favoured the opportunistic behaviour of N. asiatica . Despite the therapeutic measures, the animal died, mainly due to respiratory distress. The association of methods to improve early diagnosis, therapy procedures and prognosis of canine nocardiosis is discussed, as well as the close relationship between pets and their owners, which may favour the transmission of pathogens such as Nocardia from pets‐to‐humans, which poses an emerging public health issue. Abstract : Nocardia asiatica causing pyogranulomatous pleuropneumonia were report for the first time in a dog coinfected with canine morbillivirus.